Kesalahan Berbahasa Arab Perspektif Howard Douglas Brown: Studi Kasus Mahasiswa PTDU Malang - Ritonga, Apri Wardana; Oktavera, Hasnil; Desrani, Ayu; Ernawati, Ernawati (STAI Ali bin Abi Thalib Surabaya, 2024)
This study aims to analyze students’ Arabic language errors from Howard Douglas Brown’s perspective, identifying three errors, namely interlingual transfer, intralingual transfer, and context of learning. An interpretive paradigm and qualitative approach were used in this study using a case study method at Daarul Ukhuwwah College (PTDU), Malang. Data was collected through observation, interviews and documentation, then analyzed using qualitative analysis and data triangulation. The results of the study show that students often make mistakes in Arabic grammar, vocabulary and pronunciation according to Brown’s theory of interlingual transfer, intralingual transfer and context of learning. Students’ perceptions of language errors show a basic understanding of the second language learning process, where errors are considered as a step in understanding and using Arabic. The implications of this study include expanding understanding of the needs of Islamic boarding school students in learning Arabic as well as adapting the curriculum and teaching methods to increase the effectiveness of Arabic language learning in Islamic boarding schools.